2019
DOI: 10.21125/inted.2019.0919
|View full text |Cite
|
Sign up to set email alerts
|

Learning Experience From Teaching and Learning Methods in Engineering Education: Instructors’ Viewpoint

Abstract: Knowledge-based learning has been the emphasized pedagogy and balanced with skills-based learning in Engineering education for the last six decades. Students have learned and gained their experiences mainly from lectures, assignments, laboratory sessions, project works, and a final-year project or a dissertation. Besides pedagogy improvement, several teaching and learning methods such as problem-based learning, project-based learning, virtual classroom, etc., have been introduced and applied to offer a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, only a few -e.g., gamebased learning, project-based learning [1], problem-based learning [2], peer-to-peer learning [3], flipped classroom [4], visual laboratory [5], virtual laboratory [6], Industry 4.0 laboratory [7] -have gained popularity within specific communities. Aside from that, a recent study found that lecture is still the most commonly applied and has been dominating current teaching practices [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few -e.g., gamebased learning, project-based learning [1], problem-based learning [2], peer-to-peer learning [3], flipped classroom [4], visual laboratory [5], virtual laboratory [6], Industry 4.0 laboratory [7] -have gained popularity within specific communities. Aside from that, a recent study found that lecture is still the most commonly applied and has been dominating current teaching practices [8].…”
Section: Introductionmentioning
confidence: 99%